2012
DOI: 10.1111/j.1574-6941.2011.01269.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition of humic acid-degrading estuarine and marine bacterial communities

Abstract: We examined the bacterial decomposition of humic acids (HA) in two flowthrough culture experiments, one inoculated by marine and one by estuarine bacterial communities. In both experiments, the cultures were fed with HA media of salinities of 28 and 14, close to their ambient and a distinctly different, foreign salinity. HA were decomposed to > 60% of the initial concentration within 70 days, and the foreign salinity yielded the highest decomposition. A detrended correspondence analysis of denaturing gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 66 publications
0
41
0
Order By: Relevance
“…It has also been reported that Alphaproteobacteria and Gammaproteobacteria have been found in organic-rich sediments, such as those at fish farms, or have been provoked by organic enrichment [58][61], and even by complex humic compounds [62]. The abundant decomposing organic matter and oxygenic bacteria detected in our study, and in previous studies, may contribute greatly to nutrient release such as phosphate and ammonium from sediments, either directly from organic matter or indirectly, enhancing hypoxia and hypoxia-induced nutrient release (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that Alphaproteobacteria and Gammaproteobacteria have been found in organic-rich sediments, such as those at fish farms, or have been provoked by organic enrichment [58][61], and even by complex humic compounds [62]. The abundant decomposing organic matter and oxygenic bacteria detected in our study, and in previous studies, may contribute greatly to nutrient release such as phosphate and ammonium from sediments, either directly from organic matter or indirectly, enhancing hypoxia and hypoxia-induced nutrient release (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that Alphaproteobacteria is the main group stimulated when humic acids are specifically added to a marine bacterial community (Rocker et al 2012). …”
Section: Uncoupling Of Bacterial Community Activity and Composition Cmentioning
confidence: 99%
“…Group members are most dominant in coastal environments, including salt marshes heavily influenced by lignocellulosic vascular plant material (28). Roseobacter ubiquity and success in the oceans have been attributed, in part, to their ability to use a large repertoire of growth substrates, including aromatic compounds (29)(30)(31). Ge-nome analyses have identified several ring-cleaving pathways in roseobacters, including the box and pca pathways (30).…”
mentioning
confidence: 99%